Testing of Ferarabivac anti-rabies live vaccine for wild carnivores for its immunogenicity and protectivity - A. V. Shishkov; D. A. Lozovoy; A. V. Borisov; D. V. Mikhalishin (Ветеринария сегодня, 2020)
Rabies is one of the most important human and animal viral diseases, being one of the most dangerous zoonoses, causing damage to the central nervous system with an inevitable fatal outcome. This disease is of global concern, and it attracts special attention of international organizations (WHO, OIE, FAO, GARC) and of veterinary services in many countries around the world. A variety of anti-rabies vaccines have been used for specific rabies prevention in wild carnivores, however, the safety and effectiveness of some of them is doubtful. New, more advanced products are being developed, one of which is Ferarabivac, a live oral vaccine. The vaccine was tested for its immunogenicity and protectivity in wild carnivores. The optimal immunizing dose was 2.0 cm3, with the infectivity titre of RV-97 strain of at least 6.00 lg KKID50/cm3. Anti-rabies antibody titres detected in the blood sera of foxes and raccoon dogs 14 days post vaccination, were 0.70 ± 0.18 and 0.73 ± 0.19 IU/cm3, respectively, which provided protection against rabies virus infection (≥ 0.50 IU/cm3). Rabies virus neutralizing antibodies in foxes reached their maximum level of 4.30 ± 0.32 IU/cm3 50 days post vaccination. Antibody titres in vaccinated raccoon dogs also reached their maximum level of 4.53 ± 0.27 IU/cm3 50 days post vaccination. The minimum protective threshold levels of serum neutralizing antibodies was determined 12 months after the vaccination, and it was 0.62 ± 0.28 and 0.71 ± 0.17 IU/cm3 in foxes and raccoon dogs, respectively, which proves the necessity to perform booster vaccination one year later. No animals vaccinated against rabies with Ferarabivac live vaccine showed any clinical signs of the disease during the entire observation period following the challenge test carried out 30 days post vaccination.